2010
DOI: 10.1099/mic.0.038315-0
|View full text |Cite
|
Sign up to set email alerts
|

regT can modulate gingipain activity and response to oxidative stress in Porphyromonas gingivalis

Abstract: Recombinant VimA protein can interact with the gingipains and several other proteins that may play a role in its biogenesis in Porphyromonas gingivalis. In silico analysis of PG2096, a hypothetical protein that was shown to interact with VimA, suggests that it may have environmental stress resistance properties. To further evaluate the role(s) of PG2096, the predicted open reading frame was PCR amplified from P. gingivalis W83 and insertionally inactivated using the ermF-ermAM antibiotic-resistance cassette. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…These include antioxidant enzymes [45], Dps [69], the hemin layer [7] and enzymatic removal of deleterious products (e.g., 8-oxoguanine) caused by ROS [4,6,38]. Additionally, several response regulators have been implicated in oxidative stress resistance [17,18,86]. Taken together, there is no doubt that P. gingivalis is a robust organism that has developed numerous strategies to survive in the harsh environment of the periodontal pocket.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These include antioxidant enzymes [45], Dps [69], the hemin layer [7] and enzymatic removal of deleterious products (e.g., 8-oxoguanine) caused by ROS [4,6,38]. Additionally, several response regulators have been implicated in oxidative stress resistance [17,18,86]. Taken together, there is no doubt that P. gingivalis is a robust organism that has developed numerous strategies to survive in the harsh environment of the periodontal pocket.…”
Section: Resultsmentioning
confidence: 99%
“…These studies showed that ECF-σ factors could likely modulate the virulence potential of P. gingivalis , leading to oxidative stress resistance. There is also emerging evidence of a unique regulatory mechanism(s) for gingipain biogenesis in P. gingivalis (PG2096, designated regT ) that plays a role in regulating the gingipains at elevated temperatures [18]. RegT was shown to be involved in resistance to oxidative stress in P. gingivalis ; however, the exact mechanism is still unclear.…”
Section: Regulators Of Oxidative Stressmentioning
confidence: 99%
“…Several genes, including porR, gftB, rfa, ugdA, vimE, and vimF, have shown the importance of the O side chain polysaccharide (O-LPS) and anionic polysaccharide (A-LPS) in these processes (50,53,(61)(62)(63)66). A defect in some of these genes resulted in a complete loss of surface-associated gingipain proteinases, strong autoaggregation, and a marked increase in biofilm formation.…”
Section: Discussionmentioning
confidence: 99%
“…Because the specific functional roles of the vim genes are not yet fully defined, we cannot rule out the possibility that their modulation of other proteins could have similar mechanistic properties. Protein-protein interaction studies using the purified recombinant VimA (rVimA) showed that this protein can interact with the gingipains, HtrA, RegT, sialidase, and other proteins in P. gingivalis (2,47,61,64). Also, in addition to its role in glycosylation, the VimA protein can affect capsular synthesis, fimbrial phenotypic expression, and anchorage of several cell surface proteins (44).…”
mentioning
confidence: 99%
“…Further, the posttranslational addition of carbohydrates to the gingipains is highly variable, thus implying a role for multiple factors in this process (10). We previously reported that the VimA protein, which can modulate gingipain activity in P. gingivalis, can also interact with a putative sialidase protein (1,30,50,53). Although sialylation can be involved in protein maturation, its role, if any, in gingipain maturation/activation is unknown.…”
mentioning
confidence: 99%